Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Warung Nasi Bu Iyah Witana Harja - Ariel P Ginting; Novia Susanti (Jurnal Intelek Insan Cendikia, 2026)
Warung Nasi Bu Iyah is one of the micro, small, and medium enterprises (MSMEs) in the culinary sector that seeks to maintain its existence amid increasingly intense business competition. In this context, product quality and service quality are important factors that can influence consumer satisfaction. This study aims to examine and analyze the effect of product quality and service quality, both partially and simultaneously, on consumer satisfaction at Warung Nasi Bu Iyah Witana Harja. This research employs a quantitative research method with a survey approach. Data were collected through the distribution of questionnaires to 100 consumer respondents of Warung Nasi Bu Iyah, selected using a specific sampling technique. The collected data were analyzed using validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis. The results of the study indicate that product quality has a positive and significant effect on consumer satisfaction, as evidenced by a significance value of 0.000 < 0.05 and a t-value of 5.535 > t-table value of 1.984. In addition, service quality also has a positive and significant effect on consumer satisfaction, with a significance value of 0.000 < 0.05 and a t-value of 7.527 > t-table value of 1.984. Simultaneously, product quality and service quality have a positive and significant effect on consumer satisfaction, as proven by the F-test result showing an F-value of 28.391 > F-table value of 3.939 and a significance value of 0.000 < 0.05. These findings indicate that consistent improvements in product quality and service quality can enhance consumer satisfaction and may serve as a basis for management considerations in improving the competitiveness of Warung Nasi Bu Iyah